AB1318-HPR VAGUS NERVE STIMULATION IN PATIENTS WITH RHEUMATOID ARTHRITIS: 48 MONTH SAFETY AND EFFICACY. (2nd June 2020) - Koopman, F.; Musters, A.; Backer, M.; Gerlag, D.; Miljko, S.; Grazio, S.; Sokolovic, S.; Levine, Y.; Glass, E.; Chernoff, D.; De Vries, N.; Tak, P. P.
Abstract : Background: Rheumatoid arthritis (RA) is a disease with significant remaining unmet medical needs for better treatments. Vagus nerve stimulation (VNS) to activate the inflammatory reflex (cholinergic anti-inflammatory pathway) represents a novel experimental therapy for RA. 1 Previously, we reported that inflammatory reflex activation by VNS reduced pro-inflammatory cytokine production and improved disease activity in a 17-patient rheumatoid arthritis (RA) proof-of-concept study using a reprogrammed epilepsy stimulator2; clinical improvement was sustained for 24 months without untoward safety signals. 3 Here we report the 48 months results from this long-term observational study. Objectives: Determine the long-term safety and efficacy of VNS for the treatment of RA Methods: In the primary study, a VNS device was implanted into 17 RA patients, mostly with insufficient response to multiple conventional and biologic DMARDs, on stable background of methotrexate (≤25 mg weekly) therapy 2 . The device electrically stimulated the vagus nerve, 1-4 min/day, over a 12-week open label period. On completion, subjects were offered to enroll into a follow-up study, where the study physicians were given flexibility to alter VNS dosing parameters and/or to add a biologic disease-modifying antirheumatic drug (DMARD) to the treatment regimen to induce disease remission. Clinical disease activity measures and safety were accessed over 4 years. Results: All patients electively continued VNS treatment in the long-term follow-up study, 4 subjects withdrew prior to month 48. Reasons for discontinuation were withdrawal of consent (N=3) and adverse event due to device discomfort (N=1). At the start of the follow-up study, the mean DAS28-CRP, CDAI and HAQ-DI were significantly reduced compared to the pre-implant baseline (mean difference± SD: DAS28-CRP=-1.60± 1.13, p<0.001; CDAI=-21.19± 13.5, p<0.001; HAQ-DI=-0.44± 0.49, p<0.01), and this effect was retained through 48 months. Patients using VNS monotherapy and those using a combination of VNS with biologic DMARDs exhibited stable improvements in DAS28-CRP, CDAI and HAQ-DI at month 48 (Table 1 ). Improvements were observed for patients who both previously had an insufficient response to targeted biological therapies as well those who had an insufficient response to standard DMARDs. No association was seen between DAS28-CRP and stimulation frequency (Range= 1X-8X/day). There was no difference in the adverse events profile between the two groups. Conclusion: VNS was safe, well-tolerated, and resulted in significant and clinically important improvements in disease activity measures that were maintained over 48 months. These results support development of VNS devices as a new therapeutic option for RA treatment. References: [1]van Maanen MA, et al. Nat Rev Rheum 2009 [2]Koopman FA, et al. PNAS 2016 [3]Koopman FA, et al. Arthritis Rheum 2018 Disclosure of Interests: Frieda Koopman: None declared, Anne Musters: None declared, Marieke Backer: None declared, Danielle Gerlag Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Sanda Miljko: None declared, Simeon Grazio Speakers bureau: Abbvie., Roche, MSD, Eli Lilly, Pfizer, Mylan, Amgen, Fresenius Kabi, Stada, Berlin-Chemie, Sekib Sokolovic: None declared, Yaakov Levine Shareholder of: SetPoint Medical, Employee of: SetPoint Medical, Emmett Glass Employee of: SetPoint Medical, David Chernoff Shareholder of: SetPoint Medical, Adamas Pharmaceuticals, Olly Nutrition, NAIA Pharma, Aquinox Pharma, Consultant of: Adamas Pharmaceuticals, Olly Nutrition, NAIA Pharma, Aquinox Pharma, Crescendo Bioscience, Employee of: SetPoint Medical, Niek de Vries Grant/research support from: AbbVie, Janssen, Ergomed Clinical Research, GlaxoSmithKline, Pfizer, Boehringer Ingelheim, Roche, Consultant of: MSD, Pfizer, Paul P. Tak Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline